Skill development in freestyle kicking: Implications for instructors - Sanders, R.; Myres, K. (coachesinfo.com)
This study of freestyle kicking is the first in a series investigating the development of proper technique in swimming and the implications for improving teaching effectiveness. Lower limb movement patterns of swimmers weremeasured at various levels of swimming experience. The analysis, made at the beginning and end of an instructional period, identifies common features of novice swimmers and how they change with increasing skill. This original research has provided much new knowledge and insight into the process of becoming skilled in freestyle kicking. Instructors will be able to apply this new knowledge to improve teaching strategies.